Comprehensive clinical phenotype, genotype and therapy in Yao syndrome - Nomani, Hafsa; Wu, Song; Saif, Ashmia; Hwang, Frank; Metzger, Jane; Navetta-Modrov, Brianne; Gorevic, Peter D.; Aksentijevich, Ivona; Yao, Qingping (Frontiers in Immunology, 2024)
Objective:Yao syndrome (YAOS) is formerly called nucleotide-binding oligomerization domain containing 2 (NOD2)-associated autoinflammatory disease.We report a large cohort of YAOS.We conducted a retrospective analysis of a cohort of adult patients with systemic autoinflammatory diseases (SAIDs). All patients underwent testing for a periodic fever syndrome gene panel.Results: A total of 194 patients carried NOD2 variants, 152 patients were diagnosed with YAOS, and 42 had mixed autoinflammatory diseases with combined variants in NOD2 and other SAID-associated genes. Demographic, clinical and molecular data were summaried. In sub-group analysis of the 194 patients, individual patients were often identified to carry two or more variants that usually included IVS8+158/R702W, IVS8+158/L1007fs, IVS8+158/V955I, IVS8+158/other, or NOD2/variants in other SAID genes. Ninety-nineSome patients carried single variants. Taken together, these variants contribute to the disease in combination or individually.This largest cohort has provided comprehensive clinical and genotyping data in YAOS. Variants in the NOD2 gene can give rise to a spectrum from inflammatory bowel disease to autoinflammatory disease.This report further raises awareness of the underdiagnosed disease in the medical community.